Meta-Analysis: Effect of Probiotics on the Frequency and Duration of Diarrhea in Children Under Five - Ciptaningtyas, Wahyu Agustin Dwi; Murti, Bhisma; Rahardjo, Setyo Sri (Masters Program in Public Health, Sebelas Maret University, 2020)
Background: Digestive tract disease is still a health problem around the world, currently there are 2,544,084 cases of diarrhea in Indonesia in 2016. In the Central Java region, there are an estimated of 911,901 cases of diarrhea, while 95,635 cases of diarrhea have been handled. This study aims to estimate the magnitude of the effect of probiotics on the frequency and duration of diarrhea among toddler based on the results of a number of similar previous studies.Subjects and Method: This study was a systematic study and meta-analysis, with PICO as follows: Population= children under five. Intervention= Probiotics. Comparison= Not Probiotic. Outcome= Frequency and Duration of Diarrhea in toddlers. The articles used in this study were obtained from several databases including PubMed, Springer Link, Cochrane Database, Hindawi, Elsevier, JBBA, LWW, Google Scholar. The keywords for searching articles are as follows: